Political Contribution of the Sultanate of Ternate to Regional Government in North Maluku Province 1999-2023 - Umarama, Samad; Syaifuddin (International Journal of Science and Society, 2024)
This study aims to identify the political contribution of the Ternate Sultanate to the regional government of North Maluku province. The Ternate Sultanate has an important role in the dynamics of political power that occurs in the Maluku Kieraha region whose territory stretches across the Maluku Islands, Sulawesi, Papua, and borders of the Philippines, Australia, and Papua New Guinea. In this region, four sultanates ruled, namely Ternate, Tidore, Bacan and Jailolo. From 1999 to 2019, the Ternate Sultanate was at a crossroads along with the political dynamics in the Republic of Indonesia after the reformation. The results of this study indicate that during the observation period, the Ternate Sultanate contributed to resolving horizontal conflicts that occurred in Maluku and North Maluku, playing a role in strengthening regional autonomy in the North Maluku province, laying down a good democratic and development order for the development of the Maluku Kieraha region.